2006
DOI: 10.1021/np058114h
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids from Eschscholzia californica and Their Capacity to Inhibit Binding of [3H]8-Hydroxy-2-(di-N-propylamino)tetralin to 5-HT1A Receptors in Vitro

Abstract: A 70% ethanol extract of California poppy (Eschscholzia californica) was able to bind to 5-HT(1A) and 5-HT(7) receptors at 100 mug/mL. The subsequent isolation procedure yielded the known alkaloids californidine (1), escholtzine (2), N-methyllaurotetanine (3), caryachine (4), and O-methylcaryachine (5), along with a new pavine alkaloid, 6S,12S-neocaryachine-7-O-methyl ether N-metho salt (7). The structure of 7 was determined by spectroscopic data interpretation, while the absolute stereochemistry was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 23 publications
(37 reference statements)
1
21
0
1
Order By: Relevance
“…The presence of this alkaloid might explain anecdotal reports of “vivid dreams” and opioid-like activities observed in patients taking black cohosh [67], as well as explain its observed in vitro opioid activity [68]. Aporphine alkaloids exhibit strong serotonergic activity against the 5-HT 1A receptor [69, 70]. For example, N -methyllaurotetanine, which is an N -methyl analog of laurotetanine identified in this study, is a potent ligand for the 5-HT 1A receptor [70].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of this alkaloid might explain anecdotal reports of “vivid dreams” and opioid-like activities observed in patients taking black cohosh [67], as well as explain its observed in vitro opioid activity [68]. Aporphine alkaloids exhibit strong serotonergic activity against the 5-HT 1A receptor [69, 70]. For example, N -methyllaurotetanine, which is an N -methyl analog of laurotetanine identified in this study, is a potent ligand for the 5-HT 1A receptor [70].…”
Section: Resultsmentioning
confidence: 99%
“…Aporphine alkaloids exhibit strong serotonergic activity against the 5-HT 1A receptor [69, 70]. For example, N -methyllaurotetanine, which is an N -methyl analog of laurotetanine identified in this study, is a potent ligand for the 5-HT 1A receptor [70]. Although it has been shown that small structural changes in the aporphine ring can lead to a large change in pharmacological activity, it is likely that some of the aporphines identified in this study contribute to the serotonergic activity of black cohosh [71].…”
Section: Resultsmentioning
confidence: 99%
“…It does contain many other isoquinoline alkaloids such as: protopine, cryptopine and α-cryptopine, chelerythrine californidine, escholtzine, N-methyllaurotetanine, caryachine, O-methylcaryachine, 6S,12S-neocaryachine, laurotetamine and N-methyl laurotetamine, Chelirubine, chelidonine and homochelidonine. 5 Which can interact with opioid receptors and ease opium withdrawal and helps pain through GABA and serotonin.…”
Section: About the Plant Eschscholzia Californicamentioning
confidence: 99%
“…Among serotonergic activities, most interest has focused on 5-HT 1A and 5-HT 7 receptors, and natural aporphinoids have been used as model pharmacophores to develop novel synthetic analogs [79, 80]. For example, N -methyllaurotetanine, a methyl analog of laurotetanine identified in black cohosh, is a potent ligand against 5-HT 1A [81]. Interestingly, a recent study by de la Peña et al claims that magnoflorine possesses sedative and anxiolytic effects mediated by the GABAergic system [82].…”
Section: 5 Isoquinoline Alkaloidsmentioning
confidence: 99%